Generic lightlike submanifolds of an indefinite Kaehler manifold with an $(\ell, m)$-type metric connection - Lee, Chul Woo; Lee, Jae Won (Armenian Journal of Mathematics, 2020)
We study generic lightlike submanifolds $M$ of an indefinite Kaehler manifold $\bar{M}$ or an indefinite complex space form $\bar{M}(c)$ with an $(\ell, m)$-type metric connection subject such that the characteristic vector field $ζ$ of $\bar{M}$ belongs to our screen distribution $S(TM)$ of $M$.
Keywords: Generic lightlike submanifold; $(\ell, m)$-type metric connection; Indefinite Kaehler manifold; Indefinite complex space form